Public-sector outsourcing - Panu Poutvaara (IZA World of Labor, 2014)
Outsourcing public provision of services tends to lower labor intensity and increase its efficiency. Costs are usually lower, but quality problems can affect services like health care and residential youth care. Consumer choice has stimulated innovation in education, but the picture is ambiguous for health care. Natural monopolies are unsuitable for outsourcing. Network services (public transportation) may be outsourced through public tenders. While some jobs may be lost in the short run, the long-term effects are generally positive for a wide variety of activities.
Keywords: L33; H11; H57; I11; I21; J45; 330; public procurement; vouchers; outsourcing; health care; education; concession contracts